HOSPITALIZATION AND DISCHARGE OF THE NEONATE IN THE NEONATAL CARE UNIT: IDENTIFICATION OF PARENTS' DOUBTS - Braz de Araujo, Evelyn (2022)
Objective: To identify the doubts of parents regarding the care of their babies in the NICU in the process of hospitalization and hospital discharge. Methodology: descriptive study and qualitative approach. The research scenario was a neonatal unit of a tertiary hospital, located in the Rio de Janeiro, Brazil. The mothers and fathers of newborns admitted to the NICU, with a minimum stay of 2 weeks, and who were present in the unit, were selected, for convenience, as study participants. Data collection was performed using data obtained from the newborn's medical record and a questionnaire. Open interviews were also carried out with the parents in the first week of the newborn’s hospitalization in the NICU and in the subsequent weeks, until the week of discharge. In this research, data analysis was performed using Bardin's content analysis. Results: 10 mothers and 02 fathers of NB admitted to the NICU participated in this research. With the transcription of the interviews, seven categories emerged that dealt with the doubts that mothers and fathers had during the hospitalization process, described below: Basic Care; Breastfeeding/Feeding; Treatment; Exams/Surgeries; Disadvantages for discharge; Post-surgical care; Hospitalization time. The category with the highest number of doubts presented during the survey was Treatment (25.5%). Conclusion: It was possible to verify that the hospitalization in the NICU generates several doubts in the parents. Doubts related to the care provided to their children, about breastfeeding and feeding, about treatment, among others